FLT3/ITD AML and the law of unintended consequences - Levis, Mark (American Society of Hematology, 2011)
Acute myeloid leukemia with a FLT3 internal tandem duplication (FLT3/ITD) mutation is an aggressive hematologic malignancy with a generally poor prognosis. It can be successfully treated into remission with intensive chemotherapy, but it routinely relapses. At relapse, the blasts tend to have higher mutant allelic ratios and, in vitro, are more addicted to the aberrant signaling from the FLT3/ITD oncoprotein. They remain highly responsive to FLT3 ligand, the levels of which rise several-fold during the course of chemotherapy. The question now arises as to whether these high levels of FLT3 ligand are actually promoting relapse, and, if so, how we can use this information to adjust our therapeutic approach and improve the cure rate for acute myeloid leukemia with FLT3/ITD.